Amendments to the Constitution of the Realmof Denmark in Connection with the Accessionto the European Union - Michalska, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Realm of Denmark has constitutional traditions. The current constitution was introduced in 1953. Denmark joined the European Communities in 1972 and in 1993, in the Maastricht Treaty, Denmark contributes part of its sovereignty to the European Union on the basis of Art. 20 of the Constitutional Act. Therefore, EU legislation acting under delegated mandates to the EU can be directly applied in Denmark, depending on the specific act. In addition, the law of EU law Danish courts are obliged to respect the supremacy of EU law over Danish law. However, the Danish Supreme Court recognized the supremacy of the Danish constitution over EU law, reserving the right to consider questions as to whether an EU legal act or a decision of the European court over a waiver of exclusivity in the Accession Treaty (ultra vires control). These respect the supremacy of EU rights.
Keywords: Dania; Unia Europejska; konstytucja; poprawka do konstytucji; Denmark; European Union; constitution; amendment to the constitution